Depression as a risk factor for dementia and mild cognitive impairment: a meta-analysis of longitudinal studies - Gao, Yuan; Huang, Changquan; Zhao, Kexiang; Ma, Louyan; Qiu, Xuan; Zhang, Lei; Xiu, Yun; Chen, Lin; Lu, Wei; Huang, Chunxia; Tang, Yong; Xiao, Qian (International journal of geriatric psychiatry, 2013)
This study examined whether depression was a risk factor for onset of dementia including Alzheimer's disease (AD), vascular dementia (VD) and any dementia, and mild cognitive impairment (MCI) by using a quantitative meta-analysis of longitudinal studies. EMBASE and MEDLINE were searched for articles published up to February 2011. All studies that examined the relationship between depression and the onset of dementia or MCI were included. Pooled relative risk was calculated using fixed-effects models. Twelve studies met our inclusion criteria for this meta-analysis. All subjects were without dementia or MCI at baseline. Four, two, five, and four studies compared the incidence of AD, VD, any dementia, and MCI between subjects with or without depression, respectively. After pooling all the studies, subjects with depression had higher incidence of AD (relative risk (RR):1.66, 95% confidence interval (CI): 1.29-2.14), VD (RR: 1.89, 95% CI: 1.19-3.01), any dementia (RR: 1.55, 95% CI: 1.31-2.83), and MCI (RR: 1.97, 95% CI: 1.53-2.54) than those without depression. The quantitative meta-analysis showed that depression was a major risk factor for incidence of dementia (including AD, VD, and any dementia) and MCI.